2019
DOI: 10.15233/gfz.2018.35.7
|View full text |Cite
|
Sign up to set email alerts
|

Review and critical analysis on digital elevation models

Abstract: Nowadays, digital elevation model (DEM) acts as an inevitable component in the field of remote sensing and GIS. DEM reflects the physical surface of the earth helps to understand the nature of terrain by means of interpreting the landscape using modern techniques and high-resolution satellite images. To understand and analyze the nature of the terrain, DEM is required in many fields in the improvement of developing the product and decision making, mapping purpose, preparing 3D simulations, estimating river cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…The ASTER GDEM2 was released in 2011 and showed improvements compared with the first version, such as better georeferencing, inclusion of more scenes acquired between 2008 and 2011, and a smaller correlation kernel, and has higher spatial resolution [33]. However, ASTER GDEM2 is known to have anomalies and artifacts that limit its usefulness [9,35]. Previous studies have found that ASTER GDEM2 performs well over bare areas but is less accurate over areas with a high forest cover [30,36].…”
Section: Astermentioning
confidence: 99%
See 2 more Smart Citations
“…The ASTER GDEM2 was released in 2011 and showed improvements compared with the first version, such as better georeferencing, inclusion of more scenes acquired between 2008 and 2011, and a smaller correlation kernel, and has higher spatial resolution [33]. However, ASTER GDEM2 is known to have anomalies and artifacts that limit its usefulness [9,35]. Previous studies have found that ASTER GDEM2 performs well over bare areas but is less accurate over areas with a high forest cover [30,36].…”
Section: Astermentioning
confidence: 99%
“…Digital elevation models (DEMs) and the topographic and terrain variables derived from these models (e.g., slope aspect, slope, channels, hillslopes) are fundamental inputs for environmental and landscape modeling and spatial analysis [1][2][3][4][5], especially for research in geomorphology [6], hydrology [7], and geology [8]. For several decades, DEM products have been created at different spatial scales (e.g., global or national) mainly using remote sensing data [9]. As different remote sensing data and methods are employed during the development of DEMs, it has become increasingly important to assess the accuracy and performance of such products to provide insights into their limitations [10] and develop correction procedures [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the Unmanned Aerial Systems (UAS) technology is commonly preferred for different applications because of its pilotless carrier platform. Although Digital Elevation Models (DEMs) can be derived by conventional photogrammetry approaches, it requires aerial photographs or stereo pairs, specialist software, expertise, and extensive manual measurement of control points or features [23].…”
Section: Introductionmentioning
confidence: 99%
“…(20)(21)(22)(23)(24) A 3D light detection and ranging (LiDAR) laser scanner is a device that stores a group of point clouds of 3D coordinate components (X, Y, and Z) by calculating the return time or phase difference of the returning beam by emitting the laser beam to the measurement target. (25)(26)(27)(28) Figure 2 shows a point cloud. 3D laser scanners are used in various fields.…”
Section: Introductionmentioning
confidence: 99%